Implementasi Manajemen Waktu pada Siswa Sekolah Dasar - Putra, Alan Anditia; Daflaini, Daflaini; Pohan, Munawir (Institut Agama Islam Negeri Kerinci, 2022)
This research aims to find out thematic real work lectures (KKN) based on religious moderation for students of the State Islamic Religious Institute (IAIN) in detail